Randomized controlled trial comparing the effectiveness of tamsulosin, tamsulosin with tolterodine and double J stent position in controlling stent related symptoms after ureteroscopic lithotripsy - Agbo, Christian A.; Nahar, Guavar (International Surgery Journal, 2023)
Background: Objective of the study was to determine the effect of stent position and medications in preventing stent-related symptoms. Methods: This was a prospective study conducted at Meenakshi Mission Hospital and Research Centre Madurai, Tamil Nadu, India. 150 patients who underwent ureteroscopic lithotripsy with indwelling stent were distributed into three groups. On demand analgesics were given to group 1 (n=50), Tamsulosin 0.4 mg daily for group 2 (n=50) and tamsulosin 0.4 mg and tolterodine 4 mg daily for group 3 (n=50). The patients were also subclassified into appropriate or inappropriate group according to stent position. All patients completed various domains of Ureteral stent symptom questionnaire (USSQ) on 1st and 7th postoperative days. Appropriate tests statistics were performed using EPI-Info statistical software package. Results: In control group, patients with appropriate stent position had significantly lower symptom scores than those with inappropriate stent position (p value 0.0001) in all domains of USSQ except global quality of life score (p value=0.08). Addition of tamsulosin 0.4 mg (group 2) had superadded beneficial effect in appropriate position group, but not in patients with inappropriately positioned stents. Patients taking both tamsulosin 0.4 mg and tolterodine 4 mg (group 3) had no significant improvement in symptom scores in appropriate position group (all domains of USSQ) and inappropriate position group (most domains). Conclusions: Appropriate stent position is the most important independent factor than medications in preventing stent related symptoms; tamsulosin has superadded benefit in patients with correctly positioned stents.